Defective expression of plectin/HD1 in epidermolysis bullosa simplex with muscular dystrophy. - Gache, Y (1996)
Epidermolysis bullosa simplex with muscular dystrophy (MD-EBS) is a disease characterized by generalized blistering of the skin associated with muscular involvement. We report that the skin of three MD-EBS patients is not reactive with antibodies 6C6, 10F6, or 5B3 raised against the intermediate filament-associated protein plectin. Immunofluorescence and Western analysis of explanted MD-EBS keratinocytes confirmed a deficient expression of plectin, which, in involved skin, correlated with an impaired interaction of the keratin cytoskeleton with the hemidesmosomes. Consistent with lack of reactivity of MD-EBS skin to plectin antibodies, plectin was not detected in skeletal muscles of these patients. Impaired expression of plectin in muscle correlated with an altered labeling pattern of the muscle intermediate filament protein desmin. A deficient immunoreactivity was also observed with the monoclonal antibody HD121 raised against the hemidesmosomal protein HD1. Furthermore, immunofluorescence analysis showed that HD1 is expressed in Z-lines in normal skeletal muscle; whereas this expression is deficient in patient muscle. Colocalization of HD1 and plectin in normal skin and muscle, together with their impaired expression in MD-EBS tissues, strongly suggests that plectin and HD1 are closely related proteins. Our results therefore provide strong evidence that, in MD-EBS patients, the defective expression of plectin results in an aberrant anchorage of cytoskeletal structures in keratinocytes and muscular fibers leading to cell fragility.